Early relapse detection by monitoring of circulating cell-free DNA in patients with localized head and neck squamous cell carcinoma: A subgroup analysis of the multicenter randomized clinical trial IMSTAR-HN. (March 2022) - Jonas, Hanna; Simnica, Donjete; Bußmann, Lara; Zech, Henrike; Doescher, Johannes; Laban, Simon; Busch, Chia-Jung; Binder, Mascha
Highlights: Liquid biopsy monitoring is feasible in head and neck cancer patients. Cell-free DNA mutations after surgery identify patients at risk for early relapse. Increasing variant allele frequencies precede clinical progression.